Bright and efficient blue polymer light emitting diodes with reduced operating voltages processed entirely at low-temperature12. Issue 36 (28th September 2015) - Hoye, R. L. Z.; Musselman, K. P.; Chua, M. R.; Sadhanala, A.; Raninga, R. D.; MacManus-Driscoll, J. L.; Friend, R. H.; Credgington, D.
<x xml:space="preserve">Abstract</x> Efficient and bright blue polyfluorene LEDs, processed entirely below 150 °C, are obtained using an atmospherically synthesized, tunable oxide electron-injector.